Biocompatibility analysis and chemical characterization of Mn-doped hydroxyapatite - L. S. Villaseñor-Cerón; D. Mendoza-Anaya; S. López-Ortiz; R. Rosales-Ibañez; J. J. Rodríguez-Martínez; M. I. Reyes-Valderrama; V. Rodríguez-Lugo (Journal of Materials Science: Materials in Medicine, 2023)
Abstract The present work studies the effect of Mn doping on the crystalline structure of the Hap synthesized by the hydrothermal method at 200 °C for 24 h, from Ca(OH)2 and (NH4)2HPO4, incorporating MnCl2 to 0.1, 0.5, 1.0, 1.5 and 2.0 %wt of Mn concentrations. Samples were characterized by the X-Ray Diffraction technique, which revealed the diffraction peaks that corresponded to the hexagonal and monoclinic phase of the Hap; it was observed that the average size of crystallite decreased from 23.67 to 22.69 nm as the concentration of Mn increased. TEM shows that in all samples, there are two distributions of particle sizes; one corresponds to nanorods with several tens of nanometers in length, and the other in which the diameter and length are very close. FTIR analysis revealed absorption bands corresponding to the PO4 −3 and OH− groups characteristic of the Hap. It was possible to establish a substitution mechanism between the Mn and the ions of Ca+2 of the Hap. From the Alamar blue test, a cell viability of 86.88% ± 5 corresponding to the sample of Hap at 1.5 %wt Mn was obtained, considered non-cytotoxic according to ISO 10993-5. It also evaluated and demonstrated the good osteoinductive properties of the materials, which were verified by histology and immunofluorescence expression of osteogenic markers. Adhesion, viability, biocompatibility and osteoinductive properties, make these materials candidates for future applications in bone tissue engineering with likely uses in regenerative medicine. Graphical Abstract